Assessment of heavy metal concentrations and its potential eco-toxic effects in soils and sediments in Dong Cao catchment, Northern Vietnam - Mai, Huong; Maeghtb, Jean -Luc; Bui, Van Hoi; Valentin, Christian (Vietnam Journal of Earth Sciences, 2020)
The environmental risks associated with the concentration of metals in soils and sediments due to their toxicological properties on living organisms are not yet sufficiently studied in North Vietnam. Soil samples and sediments collected from three weirs (W1, W2 and W4) of the Dong Cao catchment (49.7 ha) and from the downstream Cua Khau reservoir (CK) were analyzed for heavy metal concentrations and geochemical parameters. Bioassays were then applied to assess the toxicity of these soils and sediments based on a test of phytotoxicity with garden cress (Lepidium savitum) and the BioTox test for toxicity to bacteria, using Allivibrio fischeri. Metal concentrations in sediments (Cr and Cu) were significantly higher in the Dong Cao catchment (W1 and W4) in comparison with the reservoir area. The toxicity of soils and sediments of W1 and W4 was detected at a low level by the two bioassay tests. Inhibition of light emission by Allivibrio fischeri was slightly reduced for soils and sediments of W1 and W4 after 15-min of the contact. Similarly, this slight impact has been reflected in the growth and seed germination of Lepidium savitum in the sediment samples collected from the weirs of Dong Cao catchment. The major pollutant metals were Cr, Cu and Zn. Cr contamination is undoubtedly derived from rocks whereas Cu and Zn are most likely associated with human activities (local agricultural inputs and atmospheric fallout).